Clinical, radiographic and haemato-biochemical study of sidebones in equine - PUROHIT, S; GAHLOT, T K (The Indian Journal of Animal Sciences, 2011)
The study was conducted in 51 horses of either sex aged between 2 to 11 years. Sidebones were diagnosed in 20 female and 5 male horses on the basis of radiographic examination. The lateral sidebones were seen in all the cases, but medial were seen only in 22 cases. Sidebones were graded on a 0–4 scale as the degree of ossification of collateral cartilage. Grade 2 was the most prevalent followed by grade 1, grade 3 and grade 4 whereas values of calcium, Ca: P ratio, carotene, serum alkaline phosphatase, calcitonin, erythrocyte sedimentation rate and packed-cell volume were significantly higher and total leucocyte count and vitamin-A were significantly (P<0.05) lower than base values. Total erythrocyte count values were not found altered.